The Effectiveness of the Virtual PhET-assisted Discovery Learning Model to Improve Students’ Science Process Skills on Collision Material - Mubayyinah Muliyadi; El Indahnia Kamariyah; Suprianto (SEJ (Science Education Journal), 2026)
This study aims to determine the effectiveness of the Virtual PhET-assisted Discovery Learning model in improving students' science process skills on collision material. This study uses a quantitative approach with a quasi-experimental method and a non-equivalent control group design. The research sample consisted of 40 students of grade XI MAN 1 Pamekasan who were divided into an experimental class and a control class, each consisting of 20 students. The sampling technique used cluster random sampling. The research instrument was a multiple-choice science process skills test consisting of a pretest and a posttest. Data analysis used the Shapiro-Wilk normality test, homogeneity test, Mann-Whitney test, and N-Gain test. The results showed that the posttest significance value in the Mann-Whitney test was 0.000 < 0.05, indicating that there was a significant difference between the experimental class and the control class after being given treatment. In addition, the results of the N-Gain test showed that the experimental class obtained an average of 91.33% with an effective category, while the control class obtained an average of 59.58% with a fairly effective category. Based on these results, it can be concluded that the Virtual PhET-assisted Discovery Learning model is effective in improving students' science process skills on collision material.